Growth and characterization of bamboo-shaped carbon nanotubes using nanocluster-assembled ZnO:Co thin films as catalyst - Tay, Beng Kang (2013)
Bamboo-shaped carbon nanotubes (CNTs) had been successfully fabricated by a plasma enhanced chemical vapor deposition method, in which nanocluster-assembled ZnO:Co thin film was used as catalyst. It was found that bamboo-shaped CNTs were generally grown in a direction perpendicularly to the substrate surface with the tops of CNTs dominated by the droplet-like catalyst covered by the carbon layer. The diameter of CNTs was ranged from 20–50 nm. High resolution of TEM image showed that the typical CNT had a multi-walled structure with an inner core presented. The ordered graphite layers were inclined to an axis of CNT about 18° and the interlayer space of a CNT was about 0.35 nm. Two peaks in Raman spectrum at 1586 cm−1 and 1372 cm−1 were identified as G-band and D-band for graphite, respectively. The results showed that catalyst based on ZnO:Co thin films could be used for the growth of CNTs with bamboo-shaped structure.